The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.6061/clinics/2012(08)06
|View full text |Cite
|
Sign up to set email alerts
|

Predicting dysthyroid optic neuropathy using computed tomography volumetric analyses of orbital structures

Abstract: OBJECTIVE:To evaluate the ability of orbital apex crowding volume measurements calculated with multidetector-computed tomography to detect dysthyroid optic neuropathy.METHODS:Ninety-three patients with Graves' orbitopathy were studied prospectively. All of the patients underwent a complete neuro-ophthalmic examination and computed tomography scanning. Volumetric measurements were calculated from axial and coronal contiguous sections using a dedicated workstation. Orbital fat and muscle volume were estimated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
0
24
1
2
Order By: Relevance
“…The results of univariate correlations for orbital metrics (including orbital volume, volumetric crowding index[15], and proptosis) and optic nerve metrics (include length, cross sectional area, volume, and diameter) are shown in Table 1. Similarly, the correlations for clinical characteristics with muscle metrics are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of univariate correlations for orbital metrics (including orbital volume, volumetric crowding index[15], and proptosis) and optic nerve metrics (include length, cross sectional area, volume, and diameter) are shown in Table 1. Similarly, the correlations for clinical characteristics with muscle metrics are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, distinct structures such as globe, nerve, muscle, and fat can be identified with a high accuracy. Extraocular muscle, bone, fat, and orbital volume indices are among the metrics used in previous study[215] as objective findings used to aide in early diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, imaging studies, such as computed tomography (CT), magnetic resonance imaging (MRI), ultrasonography (US), and colour Doppler imaging (CDI), can also be extremely important in both the diagnosis and clinical or surgical follow-up [3].…”
Section: The Dysthyroid Optic Neuropathymentioning
confidence: 99%
“…They found that patients with Graves' orbitopathy who have severe optic nerve crowding, intracranial fat prolapse and/or muscle index greater than 50% present on orbital CT scans are more likely to have coexisting optic neuropathy. An important result to cite is due to Goncalves et al [3], who targeted at assessing the ability of multi-detector CT to detect DON. The proposed study involved 93 patients who underwent a complete neuro-ophthalmic examination, as well as a CT scan.…”
Section: The Dysthyroid Optic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation